(untitled) (Pulse, 2026)
Background: Anaemia is a serious public health concern all over the world. It is a huge health burden for low and middle-income countries. Reproductive-age women, especially pregnant women, suffer a lot due to this condition and its consequences. Objective: The objective of the study is to investigate the prevalence of anaemia among hospitalized reproductive-aged women in a peripheral hospital of Bangladesh. Materials and Methods: This is a retrospective, cross-sectional study done in Shaheed Akhter Hossain BGB Hospital, Satkania, Chattogram, from June 2024 to November 2024. A total of 131 reproductive age group women (age 12-45 years) were admitted due to various problems and included in this study. Complete blood count was done and evaluated by both an automated analyzer and manual peripheral blood film examination. Results: A total of 131 reproductive-age group women were admitted to the hospital. Among them, 56 (42.74%) were found anaemic, and the 21-30 years age group patients suffered most. Women who are married (87.5%), pregnant (51.78%), and >3rd gravida (55.17%) suffer most from anaemia. Most patients 32, 57.1%) were suffering from moderate severity of anaemia, and (58.9%) were diagnosed as microcytic anaemia and most probably iron deficiency anaemia. Other causes found are various infections, polycystic ovarian disease, abortion/miscarriage, abnormal uterine bleeding, obstetric complications, etc. Conclusion: Hospitalized women of reproductive age are vulnerable due to a high rate of anaemia. It increases hospital stay, financial burden, morbidity, and mortality. Prevention of negative outcomes of anaemia can be done by proper detection of causes, early diagnosis, and treatment. Pulse Volume 17, Issue 2 2025; 5-9